Pemasangan Infus Oleh Perawat Homecare Di Masa Pandemi Covid-19 Ditinjau Dari Pendekatan Good Samaritan Law Dan Sosiological Yurisprudence - Aris Prio Agus Santoso; Sukendar Sukendar; Aknes Galih Sumirat; Dinar Aisyah Pratiwi (LPPM Universitas Duta Bangsa Surakarta, 2022)
The problem faced by partners at this time is that many nurse members experience a dilemma when carrying out health services through home visits due to limited authority while the community's need for the role of nurses is increasing due to the Covid-19 Pandemic. The purpose of this community service is to improve the performance of health workers in hospitals, update the expertise of hospital employees in handling complaints, and help solve operational problems in hospitals. The method used in this service is a literal approach, namely an action plan consisting of a set of steps to solve a problem or achieve a goal, then as a mental procedure in the form of an order of steps that uses the efforts of the creative realm to achieve certain goals. This community service will be carried out in September 2021 after obtaining approval from Educational Institutions and Partners. The output of this service is used as a community service journal published by LPPM Duta Bangsa University, Surakarta. The results of this community service are used as a reference by the PPNI Cilacap Professional Organization to be used as a reference in the formulation of policies related to the independent practice of nurses.